Puma yagouaroundi en el Sector Sauce Grande del Coto De Caza El Angolo, Piura, Perú - Freitas Córdova, Joao Diego (2025)
The first documented record of Puma yagouaroundi (É. Geoffroy Saint-Hilaire, 1803) is reported for the Coto de Caza El Angolo, a protected natural area located in Piura, northern Peru. The record was obtained on March 16, 2024, in the Sauce Grande sector, as part of a cumulative camera-trap monitoring effort totaling 8,975 camera-days. Cameras were strategically placed along trails and natural waterholes frequently used by wildlife. The Coto de Caza El Angolo forms part of the Equatorial Dry Forest, an arid ecosystem characterized by a pronounced rainy season between January and March, which significantly affects resource availability and species distribution. The presence of P. yagouaroundi increases the number of felid species documented in the area to four, alongside Puma concolor, Leopardus pardalis, and Leopardus colocola. This finding underscores the importance of the Coto as critical habitat for top-level predators and provides strong evidence of its ecological integrity and ecosystem health, particularly in the Sauce Grande sector. In addition to expanding knowledge of P. yagouaroundi’s distribution in northwestern Peru, this record highlights the effectiveness of camera traps as a wildlife monitoring tool and emphasizes the need to strengthen conservation efforts within this protected area.